PENGGUNAAN MULTIMEDIA GAME PDL BERBASIS MOBILE LEARNING TERHADAP HASIL BELAJAR SISWA DI SMP TILANGO GORONTALO - Domil, Diyanti (Universitas Tanjungpura, 2021)
he factor of low student learning achievement is the lack of students' understanding of the material being taught. Other factors that affect students’ learning achievement come from the teacher himself, in terms of how the teacher provides learning to students, also about the accuracy of the selection ofmedia used in accordance with the material being taught so that students do not feel bored. Based on this background, the purpose of this study is to determine the improvement of students’ learning achievement by using mobile learning-based Adventure in Pyramid (PDL) multimedia games. The research method used is experimental with the results obtained F * = 22,903. After being compared to the value of F table = F(0.05;1;37) = 4.105, F*= 22.903 > Ftable = 4.105, then H0 was rejected. This shows that the learning achievement of students who are taught using Mobile Learning-Based Adventure in Pyramid (PDL) multimedia games are higher than the learning achievement ofstudents who are taught using powerpoint media on pyramid material.